Rental housing and the continuum of carcerality - Reosti, Anna (Theoretical criminology, 2024)
Existing research on housing and the carceral state demonstrates a divergence in the carceral state's orientation toward property owners and the unhoused. We focus on the liminal arena of rental housing and draw on three cases—landlords’ use of criminal history to screen rental applicants, citizen participation in policing neighborhoods, and crime initiatives that weaponize building code enforcement—to posit a continuum of housing carcerality. We argue that the carceral regulation of rental housing emerges from sources in civil law and policy, illustrating the enduring relevance of what Beckett and Murakawa call the shadow carceral state. Yet, in the rental context, the carceral state tends to have a more covert, decentralized character which does not consistently align with the economic interests of rental property owners and other housing market elites in comparison to its manifestation at the ends of the continuum.